Quantitative Evaluation of Reservoir Heterogeneity in the Ordos Basin Based on Tamura Texture Features - Xiao, Zikang; Ding, Wenlong; Hao, Shiyan; Wang, Zhitao; Xu, Chong; Gao, Huiran; Zhang, Xiaolong (Frontiers in Earth Science, 2022)
The low permeability sandstone reservoir in the Ordos Basin displays heterogeneity with sedimentation and tectonic origins, which is mainly manifest by interbedding of sandstone and mudstone, bedding, and fractures. There is a clear difference between this type of heterogeneity and pore heterogeneity and diagenetic heterogeneity. At present, academia pays less attention to this kind of heterogeneity and lacks a quantitative evaluation method. The imaging log can describe this kind of heterogeneity directly. The Tamura texture features (TTF) method was used to calculate the roughness of different heterogeneous intervals. It is found that the fracture has the largest roughness, followed by the oblique bedding and the horizontal bedding section, and the massive bedding has the smallest roughness. The GR curve roughness calculated by EMD is consistent with that calculated by TTF. Therefore, TTF can be used to quantitatively evaluate the heterogeneity of low permeability sandstone reservoirs based on the imaging log when the imaging log has the same size. The roughness of the imaging log calculated by the TTF method has a strong coupling with the sedimentary cycle. This method is accurate, objective, and easy to understand. This is another important application of TTF in addition to quantitative evaluation of the heterogeneity of low permeability sandstone reservoirs.